2018
DOI: 10.1002/ijc.31910
|View full text |Cite
|
Sign up to set email alerts
|

PNPLA3 and TM6SF2 variants as risk factors of hepatocellular carcinoma across various etiologies and severity of underlying liver diseases

Abstract: Few single nucleotide polymorphisms (SNPs) have been reproducibly associated with hepatocellular carcinoma (HCC). Our aim was to test the association between nine SNPs and HCC occurrence. SNPs in genes linked to HCC (DEPDC5, GRIK1, KIF1B, STAT4, MICA, DLC1, DDX18) or to liver damage (PNPLA3‐rs738409, TM6SF2‐rs58542926) in GWAS were genotyped in discovery cohorts including 1,020 HCC, 2,021 controls with chronic liver disease and 2,484 healthy individuals and replication was performed in prospective cohorts of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
75
6
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 85 publications
(87 citation statements)
references
References 50 publications
(105 reference statements)
5
75
6
1
Order By: Relevance
“…A GWAS has identified a SNP of patatin‐like phospholipase domain‐containing 3 ( PNPLA3 ) gene rs738409, which is associated with risk of development of nonalcoholic fatty liver disease (NAFLD) . Additional studies have also reported an association with risk of developing steatosis, fibrosis, and cirrhosis attributed to high alcohol intake and also with risk of HCC on alcohol‐related liver disease (ALD) . Furthermore, transmembrane 6 superfamily 2 ( TM6SF2 ) rs58542926 has also been associated with risk of NAFLD and ALD as well as HCC .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…A GWAS has identified a SNP of patatin‐like phospholipase domain‐containing 3 ( PNPLA3 ) gene rs738409, which is associated with risk of development of nonalcoholic fatty liver disease (NAFLD) . Additional studies have also reported an association with risk of developing steatosis, fibrosis, and cirrhosis attributed to high alcohol intake and also with risk of HCC on alcohol‐related liver disease (ALD) . Furthermore, transmembrane 6 superfamily 2 ( TM6SF2 ) rs58542926 has also been associated with risk of NAFLD and ALD as well as HCC .…”
mentioning
confidence: 99%
“…Additional studies have also reported an association with risk of developing steatosis, fibrosis, and cirrhosis attributed to high alcohol intake and also with risk of HCC on alcohol‐related liver disease (ALD) . Furthermore, transmembrane 6 superfamily 2 ( TM6SF2 ) rs58542926 has also been associated with risk of NAFLD and ALD as well as HCC . The impact of PNPLA3 and TM6SF2 in HCC development on chronic hepatitis C (CHC) or B (CHB) seems to be marginal .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, while the rs738409 mutation has been convincingly associated to liver carcinogenesis in alcoholic liver disease [28,29] and in nonalcoholic steatohepatitis [30,31], this association in viral hepatitis has been the subject of controversy [32,33]. While some authors reported an increased risk of HCC development in HCV patients carrying the G allele [34][35][36][37][38], others failed to confirm these findings [4,[39][40][41][42]. The reason for this discrepancy may belong to the different ethnicities of the study populations; in fact, the largest part of the studies failing to demonstrate the association of this SNP with HCC has been conducted on Asian populations.…”
Section: Discussionmentioning
confidence: 99%
“…The DEPDC5 rs1012068 G allele was associated with a 40% increased risk of cirrhosis, OR 95%CI (1.40: 1.08-1.81; P = 0.011) [25]. Another European study genotyped for 7 SNPs (DEPDC5 rs1012068, GRIK1 rs455804, KIF1B rs17401966, STAT4 rs7574865, MICA rs2596542, DLC1 rs2275959, and DDX18 rs2551677) in 1020 HCC, 2021 chronic liver diseases (CLD) but without HCC and 2484 healthy subjects and found also no significant association of MICA or DEPDC5 with HCC development [26]. This is indicating that the role of the DEPDC5 gene in the HCC development needs further research and validation in different ethnicities.…”
Section: Depdc5 (Rs1012068) and Hccmentioning
confidence: 99%